EFEKTIVITAS PEMBELAJARAN FISIKA MELALUI PENDEKATAN OPEN-ENDED PADA MATERI LISTRIK DINAMIS TERHADAP PEMAHAMAN KONSEP FISIKA SISWA DI SMAN 10 PEKANBARU - Kitty Andriany Andriany; M. Noer '; Fakhruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine the effectiveness of physics learning by open-ended approach in lesson dynamic electric to students’ physics concept comprehension in class X5 IPA SMAN 10 Pekanbaru. The subjects were students of class X5 IPA and class X3 IPA. Class X5 IPA as eksperiment’s class totalling 40 students, consisting of 12 male students and 28 female students. While class X3 IPA as control’s class totalling 39 students, consisting of 16 male students and 23 female students. The instrument of data collection in this study is the concept comprehension test consists of 7 essay questions. Analysis of the data in this study are a descriptive analysis to see an over view of the results of the students' physics concept comprehension by using the criteria of absorption and the effectiveness and it is a inferential analysis to know there is no difference between physics learning by open-ended approach with physics learning by conventional to students’ physics concept comprehension. The analysis of the data showed: absorption eksperiment’s class average is 80,71% with a good category, otherwise learning effectiveness declared in effective. While absorption control’s class average is 75,46% with a good category, otherwise learning effectiveness declared in effective and there is difference between physics learning by open-ended approach with physics learning by conventional to students’ physics concept comprehension. Nevertheless, it can be concluded that physics learning by open-ended approach is could be used in learning process class X5 IPA SMAN 10 Pekanbaru.Key Words: open-ended approach, concept comprehension, dynamic electric